Penerapan Modul Praktikum Instalasi Motor Listrik Di SMKN 1 Darul Kamal - Didi Trianda; Sri Wahyuni; Mursyidin Mursyidin (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Education is a conscious effort to improve all forms of human resources. Vocational high school (SMK) is a level of education that prioritizes skills in certain fields. It has the main goal of preparing students to enter the workforce. SMKN 1 Darul Kamal is one of the vocational education levels which was interested by the junior high school graduates especially in terms of Electrical Installation Engineering. In class XI TITL,the students have a lot of difficulty in learning the science of Electrical Motor Installation (IML). This caused by limiting of teaching materials/printed books, that recently available in monochrome display theories and pictures. Thus, it is difficult for students to absorb their knowledge. The solution efforts should be done was applying the practicum module to assess the student learning outcomes and their responses to the electric motor installation module. This research used a quantitative approach. Based on the results of data processing, it shows that there is a different changing in students’outcomes that shown from the average score of students at the pre-test, which is 50 and the average score of students at the post-test, which was 76.25. As for the response to the electric motor installation practicum module, it showed a very high response from students, which the average of the response value was 85%.. It can be concluded that the motor installation module was effective in its application and it could be improved into other subject material.